CRM IN RETAINING CUSTOMERS TO INCREASE VISICOM STORE SALES WITH THE ANALYTICAL HIERARCHY PROCESS METHOD - Vincensius Edward Litya; Randy Permana; Shary Armonitha (Jurnal Ipteks Terapan, 2023)
Customer Relationship Management is a business strategy designed to optimize profits, income, and customer satisfaction to achieve ease of doing everything so that it is easy to access information about existing products. This development can have a good impact on business people, Customer Relationship Management (CRM) is one of the business strategies to meet these goals by combining CRM and analytic hierarchical process (AHP). For this reason, the author uses AHP to achieve this business strategy. So this study proposes combining the concept of DSS with CRM as an improvement in the company's business strategy process.By taking data at the Visicom store, the author finally gets data that can be applied to the AHP method to find product recommendations to customers.